2016
DOI: 10.1037/cou0000127
|View full text |Cite
|
Sign up to set email alerts
|

Transgender community belongingness as a mediator between strength of transgender identity and well-being.

Abstract: This study examined transgender community belongingness as a mediator between strength of transgender identity and well-being. A total of 571 transgender adults (n = 209 transgender women, n = 217 transgender men, and n = 145 nonbinary-identified individuals) completed an online survey assessing transgender community belongingness, strength of transgender identity (operationalized as the extent to which a person self-categorizes their identity as transgender and the extent to which they believe their gender tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(151 citation statements)
references
References 80 publications
7
139
2
3
Order By: Relevance
“…For individuals in either situation, movement toward either a sexual minority identity for a heterosexually-identified individual or movement toward a heterosexual identity for an individual with a sexual minority identity may change access to community support and resources, which may negatively affect health. Indeed, previous research has found that group affiliation is protective against adverse mental health for transgender individuals (Testa, Jimenez, & Rankin, 2014; White Hughto, Reisner, & Pachankis, 2015), and that transgender community belongingness is important for the mental health of transgender individuals (Barr, Budge, & Adelson, 2016). Therefore, movement away from LGBQ community, and the support associated with membership in that community, may be particularly detrimental to health for transgender men.…”
Section: Discussionmentioning
confidence: 99%
“…For individuals in either situation, movement toward either a sexual minority identity for a heterosexually-identified individual or movement toward a heterosexual identity for an individual with a sexual minority identity may change access to community support and resources, which may negatively affect health. Indeed, previous research has found that group affiliation is protective against adverse mental health for transgender individuals (Testa, Jimenez, & Rankin, 2014; White Hughto, Reisner, & Pachankis, 2015), and that transgender community belongingness is important for the mental health of transgender individuals (Barr, Budge, & Adelson, 2016). Therefore, movement away from LGBQ community, and the support associated with membership in that community, may be particularly detrimental to health for transgender men.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies, greater levels of social support and quality relationships led to better coping and enhanced mental health (Budge et al., ; Dargie et al., ). One study that investigated community belongingness (Barr et al., ) helped to confirm the theory that shared social connectedness with community members is a crucial factor in experiencing a sense of identity and support. People who strongly identify as transgender had a greater sense of “belongingness” through a shared social connectedness with transgender community members and felt “greater well‐being” (Barr et al., ).…”
Section: Resultsmentioning
confidence: 95%
“…It is also evident from this review that many transgender people experience mental illness by way of depression and anxiety disorders, with scope for effective assessment and treatment of these conditions, with an associated positive impact on both mental health and well‐being and community engagement (Barr et al., ). Practitioners should therefore be more therapeutically affirmative in their approach and examine their own prejudices and beliefs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TCB, also developed by Barr and colleagues (2016), assesses how connected an individual is to the transgender community. The TCB helps clinicians and researchers understand the social connectedness and support that the individual has for their transgender identity.…”
Section: Review Of Measuresmentioning
confidence: 99%